Transforming Learning in the Digital Age: Examining the Role of AI for Catholic Religious Education Teachers (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study aims to understand the perception and utilization of artificial intelligence (AI) by Catholic Religious Education teachers in learning, as well as identify factors that influence the effectiveness of using this technology. The role of AI in the era of technology 5.0 is not only as a tool, but also as a breakthrough that helps in designing innovative learning. However, many teachers still lack the ability to utilize AI appropriately. Based on this condition, it is necessary to conduct an in-depth study related to teachers' perceptions and their ability to utilize AI in learning, especially in Catholic religious education. A qualitative research method with a phenomenological approach was used to explore the experiences and views of teachers from various levels of tenure. Data were collected through semi-structured interviews, participatory observation, and documentation, then analyzed using thematic analysis techniques and data triangulation to increase the validity of the findings. The results show that there are variations in perceptions related to AI, where teachers with less than five years of service tend to be more open and actively use AI in learning, while teachers with more than 15 years of service show skepticism and limited use. The main influencing factors were technical skills and anxiety related to changing teacher roles as well as the unsuitability of AI in conveying the spiritual and moral values of Catholicism. Training limitations and lack of in-depth understanding of AI were also significant barriers to its utilization. This study highlights the importance of continuous training that integrates technical aspects and religious values to improve teacher readiness. In addition, there is a need to develop AI content that is in line with Catholic teachings as well as learning approaches that emphasize the role of the teacher as a moral and spiritual guide. This research provides a basis for developing teacher professional development strategies and AI-based learning innovations that are aligned with the values of faith in religious education.